HPV Prevalence in Colombian Women with Cervical Cancer: Implications for Vaccination in a Developing Country - Raúl Murillo; Mónica Molano; Gilberto Martínez; Juan-Carlos Mejía; Oscar Gamboa (Hindawi Limited, 2009)
Human Papillomavirus (HPV) vaccines have been considered potentially cost-effective for the reduction of cervical cancer burden in developing countries; their effectiveness in a public health setting continues to be researched. We conducted an HPV prevalence survey among Colombian women with invasive cancer. Paraffin-embedded biopsies were obtained from one high-risk and one low-middle-risk regions. GP5+/GP6+ L1 primers, RLB assays, and E7 type specific PCR were used for HPV-DNA detection. 217 cases were analyzed with 97.7% HPV detection rate. HPV-16/18 prevalence was 63.1%; HPV-18 had lower occurrence in the high-risk population (13.8% versus 9.6%) allowing for the participation of less common HPV types; HPV-45 was present mainly in women under 50 and age-specific HPV type prevalence revealed significant differences. Multiple high-risk infections appeared in 16.6% of cases and represent a chance of replacement. Age-specific HPV prevalence and multiple high-risk infections might influence vaccine impact. Both factors highlight the role of HPVs other than 16/18, which should be considered in cost-effectiveness analyses for potential vaccine impact.